IMPROVING SPEAKING SKILL THROUGH GRAMMAR TRANSLATION METHOD AT SMAN 3 PARE PARE - Nasir, Aco (Study Program of English Literature, 2018)
The objectives of the research were to find out whether or not Communicative Grammar Translation Method can significantly enrich the students’ speaking skill. The research employed pre experimental method with one group pre-test and post-test design. The procedure of collecting data involved administrating pre-test before applying the method and posttest after applying the method. The population of the research was 90 students. The sample was taken by using Random sampling technique, were the researcher choose one class with one class consist of 15 students. The result of the research was the mean score of the students’ speaking ability before using a communicative Grammar Translation Method was 7,33and classified are poor while after applying the method the mean score was 13,06 and classified are very good to find out the different between pre test and post test , the researched applying T-test. T-test value got 9,11492486 it was concluded with the t-table value were N=15 with the degree of freedom (df), 15-1= 14 were t-table (9,11492486> 2,131) stated that the data were very strong. Because t-test value is gather then t-table value it means the (H0) is rejected and (H1) accepted. Then the writer concludes that using a communicative Grammar translation Method able to improve students’ speakingability in SMAN 3 Parepare